Principles and practicalities for measuring child poverty in the rich countries - Miles Corak (Luxembourg Income Study (LIS), 2005)
This paper has three objectives. The first is to discuss the major issues involved in defining and measuring child poverty. The choices that must be made are clarified, and a set of six principles to serve as a guide for public policy are stated. The second objective is to take stock of child poverty and changes in child poverty in the majority of OECD countries since about 1990 when the Convention on the Rights of the Child came into force. Finally, the third objective is to formulate a number of suggestions for the setting of credible targets for the elimination of child poverty in the rich countries. This involves a method for embodying the ideal of children having priority on social resources into a particular set of child poverty reduction targets, it involves the development of appropriate and timely information sources, and finally it involves the clarification of feasible targets that may vary across the OECD. Child poverty rates vary by more than a factor of ten across the OECD, from less than three percent to over 20 and almost 30%. These countries fall into four broad groups, those with child poverty rates less than 5%, those with higher rates but still less than 10%, those with rates higher than 10% and as high as 20%, and finally two countries with more than one-in-five children being poor. In the strong majority of countries child poverty rates have actually gone up. In 16 of 24 OECD countries the child poverty rate at the end of the 1990s was higher than at the beginning, and in only three countries has it declined to a measurable degree. An important challenge in reversing this trend concerns the need to develop a clear definition of child poverty for public policy in specific national contexts and to set feasible and credible targets. Economic theory, accepted statistical practice and best practice in the OECD suggest the following six principles to guide decision making: (1) avoid unnecessary complexity by using an income based measure of resources; (2) complement this by measuring material deprivation directly using a small set of indicators; (3) draw poverty lines with regard to social norms; (4) establish a regular monitoring system and update poverty lines within a five year period; (5) set a both a backstop and a target by using fixed and moving poverty lines; and (6) offer leadership and build public support for poverty reduction.
Keywords: 330; Armut; Kinder; Messung; Armutsbekämpfung; OECD-Staaten